2020
DOI: 10.1371/journal.pone.0227875
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Bacillus anthracis strains circulating in Italy from 1972 to 2018

Abstract: In Italy anthrax is an endemic disease, with a few outbreaks occurring almost every year. We surveyed 234 B. anthracis strains from animals (n = 196), humans (n = 3) and the environment (n = 35) isolated during Italian outbreaks in the years 1972-2018. Despite the considerable genetic homogeneity of B. anthracis, the strains were effectively differentiated using canonical single nucleotide polymorphisms (CanSNPs) assay and multiple-locus variable-number tandem repeat analysis (MLVA). The phylogenetic identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…IMBa003 was obtained from sheep in 1974, and it occupied the basal node of in clade V of the phylogenetic tree, referring to it as a potential ancestor strain for those from Inner Mongolia. Similarly, the genetic characterization of 234 B. anthracis strains circulating in Italy showed that most of the genotypes are genetically similar, supporting the hypothesis that all strains evolved from a local common ancestral strain (Rondinone et al., 2020). Moreover, genetic homogeneity among Vietnamese B. anthracis strains was high, and the phylogeny from core genome SNPs revealed that the Vietnamese strains were positioned close to each other (Hoang et al., 2020).…”
Section: Discussionsupporting
confidence: 58%
“…IMBa003 was obtained from sheep in 1974, and it occupied the basal node of in clade V of the phylogenetic tree, referring to it as a potential ancestor strain for those from Inner Mongolia. Similarly, the genetic characterization of 234 B. anthracis strains circulating in Italy showed that most of the genotypes are genetically similar, supporting the hypothesis that all strains evolved from a local common ancestral strain (Rondinone et al., 2020). Moreover, genetic homogeneity among Vietnamese B. anthracis strains was high, and the phylogeny from core genome SNPs revealed that the Vietnamese strains were positioned close to each other (Hoang et al., 2020).…”
Section: Discussionsupporting
confidence: 58%
“…The disease is sporadic in regions of Central Italy, islands and south of the country ( Table 6 ). In contrast, in North Italy only a few cases were recorded and genotyping of isolated strains related this occurrence to animal introductions from abroad ( 20 ).…”
Section: Cattle Diseases Without a Control Program In Italymentioning
confidence: 99%
“…The proposed interpretation for the emergence of the TEA 011 polytomy is that an outbreak occurred in one of the three European countries contributing founder lineages and that representatives were brought back in the other countries as a side effect of military operations. Southern Italy is the best candidate for being the place of the onset of the polytomy as lineages from the progenitor TEA 008/011 (7) are present in Sicilia (33). Figure 3 also suggests that the topology of TEA 011 reflects two layers of Spanish-French-Italian interactions.…”
Section: Analysing the Abr011/009 Polytomy (Tea 011)mentioning
confidence: 94%